2019
DOI: 10.1002/ppul.24487
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term respiratory outcomes in neonates with ventilator‐associated pneumonia

Abstract: Background and Objective Ventilator‐associated pneumonia (VAP) is a common nosocomial infection in critical care settings and might have important long‐term consequences in neonates. Our aim is to clarify the short‐ and long‐term respiratory outcomes of neonates affected by VAP. Methods Prospective, population‐based, cohort study with 12 months follow‐up based on clinical examinations and diary‐based respiratory morbidity score, conducted in an academic tertiary referral neonatal unit with dedicated follow‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
3
20
4
Order By: Relevance
“…The crude mortality rate between VAP and non-VAP groups in this study were 6.0% and 8.8%, which were lower than the comparable pooled crude mortality rates from the INICC during 2012-2017 (25.8% and 9.5%, respectively). 4 The VFDs of the VAP group (median 5, IQR 0-16 days) in our study was lower than reported in a previous neonatal study (median 11, IQR 5-17.7 days) 13 and adult study (average 11 [95% CI, 0-24]) 18 , but the VFDs of the non-VAP group (median 24, IQR 20-26 days) was similar to another study (median 22, IQR 14-24 days). 13 Our VAP incidence density was 10.86 per 1,000 ventilator-days, similar to previous Spanish (10.9) and Iranian (11.6) studies, 6,17 but lower than earlier French (17.1) and Egyptian (29.2) studies 13,26 and higher than the INICC report (7.5, 95% CI 6.9-8.1).…”
Section: Discussioncontrasting
confidence: 63%
“…The crude mortality rate between VAP and non-VAP groups in this study were 6.0% and 8.8%, which were lower than the comparable pooled crude mortality rates from the INICC during 2012-2017 (25.8% and 9.5%, respectively). 4 The VFDs of the VAP group (median 5, IQR 0-16 days) in our study was lower than reported in a previous neonatal study (median 11, IQR 5-17.7 days) 13 and adult study (average 11 [95% CI, 0-24]) 18 , but the VFDs of the non-VAP group (median 24, IQR 20-26 days) was similar to another study (median 22, IQR 14-24 days). 13 Our VAP incidence density was 10.86 per 1,000 ventilator-days, similar to previous Spanish (10.9) and Iranian (11.6) studies, 6,17 but lower than earlier French (17.1) and Egyptian (29.2) studies 13,26 and higher than the INICC report (7.5, 95% CI 6.9-8.1).…”
Section: Discussioncontrasting
confidence: 63%
“…The secondary objective was to assess the different levels of oxygen exposure in early life for each group. Other secondary outcomes were SpO 2 /FiO 2 ratio (S/F ratio) after surfactant therapy (see below), the need for mechanical ventilation (MV) (defined as MV during the first 3 days of life [18]), duration of invasive and non-invasive mechanical ventilation, ventilator-free days [19], duration of supplemental oxygen requirements, length of stay in the NICU and bronchopulmonary dysplasia [20].…”
Section: Objectivesmentioning
confidence: 99%
“…These complications were considered to be related to the procedure if they were recorded during the next 30 min after the surfactant therapy. Ventilator-free days were calculated as the number of days in the NICU without invasive mechanical ventilation, within the first 28 days of life; this number is zero for patients who died in the NICU [19].…”
Section: General Patient Managementmentioning
confidence: 99%
“…VAP is associated with increased morbidity, mortality, and prolonged length of hospital stay [ 7 ] representing a significant economic burden for the health system and the families [ 8 ].…”
Section: Introductionmentioning
confidence: 99%